2017
DOI: 10.1097/j.pain.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a risk factor for common mental disorders. Results from the Netherlands Mental Health Survey and Incidence Study-2: a longitudinal, population-based study

Abstract: Pain might be an important risk factor for common mental disorders. Insight into the longitudinal association between pain and common mental disorders in the general adult population could help improve prevention and treatment strategies. Data were used from the first 2 waves of the Netherlands Mental Health Survey and Incidence Study-2, a psychiatric epidemiological cohort study among the Dutch general population aged 18 to 64 years at baseline (N = 5303). Persons without a mental disorder 12 months before ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…A recent prospective cohort study examining over 5000 adults free of depression or anxiety disorders at baseline indicated that any degree of pain severity or pain interference doubled the risk of developing depression or anxiety over the 3-year follow-up period, compared to no pain at baseline. 32 Another prospective cohort study of over 2000 older adults demonstrated that chronic pain at baseline was associated with new-onset depression at 12-year follow up, but that depression at baseline was not significantly associated with new-onset chronic pain. 33 These studies do not support the view that pain is an expression of psychological distress, but rather, that pain and mood imbalances mutually influence each other and may co-occur in part due to common neurobiological vulnerabilities.…”
Section: Temporal Influencementioning
confidence: 99%
“…A recent prospective cohort study examining over 5000 adults free of depression or anxiety disorders at baseline indicated that any degree of pain severity or pain interference doubled the risk of developing depression or anxiety over the 3-year follow-up period, compared to no pain at baseline. 32 Another prospective cohort study of over 2000 older adults demonstrated that chronic pain at baseline was associated with new-onset depression at 12-year follow up, but that depression at baseline was not significantly associated with new-onset chronic pain. 33 These studies do not support the view that pain is an expression of psychological distress, but rather, that pain and mood imbalances mutually influence each other and may co-occur in part due to common neurobiological vulnerabilities.…”
Section: Temporal Influencementioning
confidence: 99%
“…Within this study, de Heer et al report a near 2-fold increase in the odds ratio of individuals with moderate to very severe pain developing mood disorders (OR = 2.10, 95% CI = 1.33-3.29) or anxiety disorders (OR = 2.12, 95% CI = 1.30-3.54) over the normal population. 16 Additionally, individuals reporting moderate to severe interference due to pain were also almost twice as likely to develop a mood disorder or anxiety within 3 years. 16 Evidence of pain’s contribution to mood disorders may also be reflected in the 37% to 48% spontaneous improvement in mood disorders reported following successful surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Additionally, individuals reporting moderate to severe interference due to pain were also almost twice as likely to develop a mood disorder or anxiety within 3 years. 16 Evidence of pain’s contribution to mood disorders may also be reflected in the 37% to 48% spontaneous improvement in mood disorders reported following successful surgery. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…The experience of pain is known to have a substantial detrimental impact on an individual's quality of life and mental health status. Extensive research has documented the high correlation between pain and mental health difficulties, not just within clinical cohorts but also in community-based studies [6]. Pain can therefore be seen as an important risk factor for the development of psychiatric conditions, for instance, depression.…”
Section: Introductionmentioning
confidence: 99%